Q. 325.0( 4 Votes )

# Factorize:

ab(x^{2} + 1) + x(a^{2} + b^{2})

Answer :

We have,

At first, we’ll take common from the expression

= abx^{2} + ab + a^{2}x + b^{2}x

= abx^{2} + a^{2}x + ab + b^{2}x

= ax (bx + a) + b (bx + a)

= (bx + a) (ax + b)

Hence,

The given expression can be factorized as:

Rate this question :

Factorize:

x^{3} – 2x^{2}y + 3xy^{2} – 6y^{3}

Find the value of a for which the polynomial is divisible by (x+3).

RS Aggarwal & V Aggarwal - MathematicsFactorize:

a^{2} + a – 3a^{2} - 3

Factorize:

2a(x + y) -3b(x + y)

RS Aggarwal & V Aggarwal - MathematicsFactorize:

8 – 4a – 2a^{3} + a^{4}

If 𝑎 + 𝑏 + 𝑐 = 9 and 𝑎𝑏 + 𝑏𝑐 + 𝑐𝑎 = 26, find 𝑎^{2} + 𝑏^{2} + 𝑐^{2}.

In each of the following, use factor theorem to find whether polynomial *g*(*x*) is a factor of polynomial *f*(*x*) or, not:

*f*(*x*) = *x*^{3}-6*x*^{2}+11*x*-6, *g*(*x*) = *x*-3

Show that p – 1 is a factor of p^{10} – 1 and also of p^{11} – 1.

Factorize:

a^{2} + ab(b + 1) + b^{3}